Sense of coherence as a predictor of health behaviors in a group of smokers - Marzec, Alicja; Andruszkiewicz, Anna; Banaszkiewicz, Mariola; Nowik, Marta (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Smoking cigarettes is a serious health problem and can cause many social diseases. Sense of coherence is a resource which can be an important predictor of health behaviors. Aim. The main objective of this research was to assess the relationship between sense of coherence of smokers and health behaviors taken by them. Material and methods. The group consisted of 221 smokers. IHB questionnaire to assess health behaviors, SOC-29 by Antonovsky to assess sense of coherence, Fagerström test to determine the type of addiction and Schneider test to assess motivation to quit smoking were used to study. Results. The average value of a global sense of coherence in the group was 132.51 with SD = 26.16. It was a slight decrease in the tendency to health behaviors. The women do not differ in health behavior due to the type of dependence which was measured by the Fagerström test. The smoking men differ in terms of one type of health behavior — proper eating habits. People with higher rates of health behaviors in a group of smokers have a higher sense of coherence than people with a lower rate of health behaviors. Conclusions. Sense of coherence plays very important role in taking health behavior, but only in the group of smoking man. In the group of smoking women the role of this predictor is much smaller. Nursing Topics 2014; 22 (2): 123–129